SEM characterization of Natural Reactive Phosphorus encapsulated by coating polymer, with controlled release (Research, Society and Development, 2024)
The vegetable polymer was developed in order to have better performance in terms of diffusion-controlled release and porosity between the reactive natural phosphate P2O5 and the polymeric material. The biomaterial in question is an additive that forms a composite from biopolymerization. However, the economy of use and the release of Nitrogen, Carbon, Calcium, Phosphorus and Potassium are a source of mechanism route. According to Callister (2009), polymers are chains of monomers that are called oligomers. releasing Nitrogen in the form of adsorption and desorption for a controlled release. According to Fick's law, reactions close to zero or greater than zero are considered non-chemical reactions. Chemical fractions without reactions.